« DE LA PRISE EN CHARGE DES NOUVEAU–NES PREMATURES AU NOUVEAU VILLAGE DE PEDIATRIE A KISANGANI » - KIKWATA , AMOSI KIKWATA G.H.; NDEMBE , ABEDI J.; GEANDJAWALALA M.; IUNGBI SINGA A.; NGANGA MAKOYI F.; TEBANDITE KASAI E. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
In 2015, the World Health Organisation (WHO) has estimated that 15 million newborns are born prematurely each year. Today, the number of premature babies is only increasing and nearly one million babies die from it. The objective of this study is to determine the frequency and complications of prematurity and to evaluate the management of this condition in Kisangani, in the Democratic Republic of Congo. A descriptive cross-sectional study was conducted from January 1, 2015 to December 31, 2016 on the registration data of premature babies followed in the New Paediatric Village. Prematurity in the New Pediatric Village accounted for 11.2%. The male sex predominated over the female sex at 52.1% compared to 47.9%. The gestational age between 33 and 36 years of age was predominant in 61% of premature babies. Glucose serum 10% was systematically administered. 30.4% of premature babies had benefited from respiratory assistance. The overall rate of successful rearing was 47.8% compared to 34.7% of deaths. Although the success rate for the rearing of premature babies was 47.8%, the death rate remains high in our environment.